Increased risk for head and neck squamous cell carcinoma in men with Crohn’s disease – a nation-wide register study - Harjunen, Anni; Puolakkainen, Enna (My University, 2020)
Inflammatory bowel disease (IBD) has been suggested to be associated with increased risk of head and neck squamous cell carcinoma (HNSCC). We performed a retrospective nation-wide register- based study of Finnish individuals diagnosed with IBD (ICD-10 codes K50 and K51) between the years 1995 and 2015. The standardized incidence ratio (SIR) of HNSCC was calculated by taking the cohort’s complementary age-year-gender-person-year comparable incidence (per 100 000 person- years) from the whole Finnish population. Altogether, 70,567 patients were diagnosed with IBD during the 20-year period. Crohn’s disease was diagnosed in 19,694 (10,335 women, 9,359 men) patients. Ulcerative colitis was diagnosed in 50,873 (24,347 women, 26,526 men) IBD patients. Altogether 89 patients with IBD were later diagnosed with HNSCC (ICD-O-3 C00-14). HNSCC occurred in 28 Crohn’s disease patients (8 women, 20 men) and to 61 colitis ulcerosa patients (22 women, 39 men). The mean time from the IBD-diagnosis to the HNSCC-diagnosis was 6.82 years. According to SIR calculations, a significantly increased risk was found in men with Crohn’s disease compared to the Finnish population expectations.

Tulehduksellisten suolistosairauksien (IBD) on esitetty lisäävän riskiä pään ja kaulan alueen syövälle. Suoritimme retrospektiivisen valtakunnallisen rekistereihin pohjautuvan tutkimuksen, johon kerättiin täysi-ikäiset suomalaiset IBD-potilaat (ICD-10 K50,K51) vuosilta 1995-2015. Vakioitu ilmaantuvuussuhde (SIR) on laskettu ottamalla koko Suomen populaatiosta kohortin vastaavia ikä-vuosi-sukupuoli-henkilövuosia vastaava ilmaantuvuus (100 000 henkilövuotta kohti). Kaiken kaikkiaan 70.567 potilasta sai IBD-diagnoosin 20 seurantavuoden aikana. Crohnin tauti diagnosoitiin 19.694 potilaalla (10.335 naista, 9.359 miestä). Haavainen paksusuolen tulehdus diagnosoitiin 50.873 potilaalla (24.347 naista, 26.526 miestä). IBD-potilaista 89 todettiin myöhemmin pään ja kaulan alueen syöpä (ICD-O-3 C00-14), joista 28 todettiin Crohnin tautia sairastavilla potilailla (8 naista, 20 miestä) ja 61 haavaista paksusuolentulehdusta sairastavilla potilailla (22 naista, 39 miestä). Keskimääräinen aika IBD-diagnoosista pään ja kaulan alueen levyepiteelikarsinoomaan oli 6.82 vuotta. SIR-laskelmien mukaan Crohnin tautia sairastavilla miehillä todettiin tilastollisesti merkitsevästi suurentunut riski sairastua pään ja kaulan alueen levyepiteelikarsinoomaan verrattuna Suomen muuhun väestöön.
Keywords: Inflammatory bowel disease, Crohn’s disease, Ulcerative colitis, Oral Cancer, Head and neck, Squamous cell carcinoma